Twenty-year experience of examining biopsies of signal lymph nodes in breast cancer - V. F. Semiglazov; P. V. Krivorotko; E. K. Zhiltsova; S. V. Kanaev; E. S. Trufanova; P. I. Krzhivitskiy; A. V. Komyakhov; T. T. Tabagua; K. S. Nikolaev; A. A. Bessonov; V. G. Ivanov; L. P. Gigolaeva; et al. (Опухоли женской репродуктивной системы, 2020)
Biopsy of signal (sentinel) lymph nodes (LN) has been performed at the N.N. Petrov National Medical Research Oncology Center, Ministry of Health of Russia, for almost 20 years. In the first few years, contrast-visual method (1 % blue isosulfan and triphenyl methane control) was used in 640 patients with early (T1–2N0M0) breast cancer. In 150 patients from this cohort, standard axillary dissection was performed irrespectively of the results of signal (sentinel) biopsy. The rate of false positive responses varied between 4.6 and 6.6 %. Since 2012, radioisotope method of visualization of signal LN with intratumor administration of 99mТс-technephyte colloid particles has been used (in 708 patients with T1–3N0M0 breast cancer). This type of signal LN biopsy had the following diagnostic characteristics: sensitivity was 58.9 %, specificity was 96.2 %, diagnostic accuracy was 87.1 %.In parallel with this study, in 2016 a study of diagnostic accuracy and safety of biopsy of axillary LN after neoadjuvant systemic therapy was started. The study included 263 patients with T1N1–3M0, T2–3N0–3M0, T4N0–1M0 breast cancer. To evaluate clinical status of axillary LN, ultrasound, single-photon emission computed tomography, mammography at baseline and after completion of neoadjuvant chemotherapy ± targeted therapy (trastuzumab) were performed. In some patients, in the recent years a double method of signal LN labeling (radioisotope and fluorescent methods) was used.In patients with baseline cN+-status, the rate of false positive signal LN biopsy conclusions was 13.6 %, in patients with baseline cN0-status it was 7.7 %.The study of double contrast of axillary LN and targeted label of metastatic LN prior to neoadjuvant systemic therapy continues. In total, various modifications of biopsy of signal LN were performed in 2,000 patients with breast cancer.The study protocol was approved by the biomedical ethics committee of N.N. Petrov National Medical Research Oncology Center, Ministry of Health of Russia.All patients gave written informed consent to participate in the study.